Fabrication and Optimization of a Silodosin In Situ-Forming PLGA Implants for the Treatment of Benign Prostatic Hyperplasia: In Vitro and In Vivo Study - Rabab A. Husseini; Tarek M. Ibrahim; Eslam Hamed; Eman Gomaa; Mennatullah M. Faisal; Ghadeer Wan; Manna Amin; Ali M. Alkolaib; Dina M. Abdelnabi (MDPI AG, 2024)
Objectives: Lower urinary tract symptoms (LUTSs) related to benign prostatic hyperplasia (BPH) are common in older men, and alpha-adrenoceptor blockers continue to be a key part of managing these symptoms. This study aimed to formulate injectable poly (lactic-co-glycolic acid) (PLGA) in situ-forming implants (ISFIs) loaded with silodosin (SLD) to address symptoms associated with BPH. This method, which ensures prolonged therapeutic effects of SLD, is intended to decrease dosing frequency and improve treatment outcomes, leading to better patient adherence. Methods: An appropriate solvent with favorable PLGA solubility, viscosity, and in vitro release profile was selected. Additionally, an I-optimal design was employed as an optimization technique. An in vivo study in albino male rats was conducted to investigate prostate-specific antigens (PSAs), prostate weight and prostatic index, histopathology, and SLD pharmacokinetics. Results: The optimized formulation showed experimental values of 29.25% for the initial burst after 2 h and 58.23% for the cumulative release of SLD after 10 days. Pharmacokinetic data revealed that the SLD-ISFI formulation had lower Cmax and higher AUC values than subcutaneous (SC) pure SLD and oral commercial SLD capsule, indicating the controlled-release impact and improved bioavailability of the ISFI systems. SLD-ISFI produced a marked drop in the prostatic index by 2.09-fold compared to the positive control. Serum PSA level decreased significantly from 0.345 ± 0.007 to 0.145 ± 0.015 ng/mL after SLD-ISFI injection compared to the positive control. Conclusions: This study indicated that the optimized SLD-ISFI formulation proved its efficacy in managing BPH.